Mechanistic insights and mitigation strategies for brominated dioxin formation from thermal treatment of hexabromocyclododecane waste - Heng Zhang; Lyumeng Ye; Junkai Lin; Zhiyuan Xu; Rong Jin; Dongyao Chen; Xin Zhou; Bingcheng Lin; Minghui Zheng (Waste Management, 2026)

Fe2+ alters carbon and nitrogen metabolic networks in a composite microbial consortium: Metagenomic insights into the shift from denitrification to DNRA - Lin Zhang; Bowei Zhao; Xiao Zhang; Yuan Li; Haibo Li; Shuying Yuan; Haoxiang Ning; Bingcheng Lv; Le Li; Xiaojun Fan; Xiuping Yue (Environmental Research, 2026)

Chlorinated and brominated persistent organic pollutants in industrial thermal processes: Emission profiles and radical-mediated formation pathways - Junkai Lin; Bingcheng Lin; Zhiyuan Xu; Guohua Zhu; Rong Jin; Lyumeng Ye; Dongyao Chen; Xin Zhou; Minghui Zheng (Journal of Environmental Sciences, 2026)

Spatiotemporal variations of chlorinated polycyclic aromatic hydrocarbons in Yellow Sea sediments: An eight-year field monitoring study - Xin Yang; Yunyong She; Qian Zhao; Dan Xu; Shenjie Li; Yueyao Yang; Guohua Zhu; Zhefu Yu; Junpeng Li; Bingcheng Lin; Minghui Zheng; Rong Jin (Journal of Hazardous Materials, 2026)

Elimination performance of NOx and chlorobenzene over VOx/TiO2-based commercial SCR catalysts at low temperature: Sulfur poisoning and regeneration - Yunfeng Ma; Jiayao Wu; Jianwen Lai; Hongbo Qi; Fanxiang Meng; Bingcheng Lin; Rong Jin; Zhongkang Han; Minghui Zheng; Xiaodong Li; Xiaoqing Lin (Chemical Engineering Journal, 2026)

Upcycling plastic waste into high-value gases via pulsed joule heating for economic and carbon benefits - Zitong Wan; Xuan Xie; Yunfeng Ma; Guohua Zhu; Rong Jin; Bingcheng Lin; Minghui Zheng (Chemical Engineering Journal, 2025)

A field UAV system (FUAS) with dual spectrometers for BRDF measurement - Xiuqing Hu; Xingwei He; Yuechao Sheng; Na Xu; Lin Chen; Wenjie Hu; Bingcheng Tao; Lu Zhang; Ling Wang; Yuqing He; Zhongqiu Sun (International Journal of Remote Sensing, 2025)

Insight into deactivation mechanism of Pd/Al2O3 catalyst during accelerated hydrothermal aging process - Bingcheng Wu; Yaliu Zhang; Wenhu Yang; Chengsong Huang; Yang Wu; Lin Zhong; Yi Jiao; Jianli Wang; Yaoqiang Chen (Fuel, 2025)

Joule heating-driven efficient catalytic oxidation of chlorobenzene over MnCe-nickel foam: A flexible and energy-efficient strategy - Fanxiang Meng; Yunfeng Ma; Xiaojun Ma; Ling Wang; Feiyi Zhou; Bingcheng Lin; Rong Jin; Minghui Zheng; Chen Sun; Tong Chen (Chemical Engineering Journal, 2025)

Variation profiles, formation mechanisms, and emission risks of brominated flame retardant compounds during cement kiln co-processing of hexabromocyclododecane-containing waste - Xin Li; Yahui Liu; Bingcheng Lin; Guohua Zhu; Jian Wang; Xiao Wang; Yueyao Yang; Shanshan Zhang; Guorui Liu; Rong Jin; Minghui Zheng (Journal of Hazardous Materials, 2024)

Corrigendum to “Magnesium-endowed exceptional hydrothermal stability of Pd/CeO2-ZrO2-Al2O3 catalyst for low-concentration methane combustion via two-step structure transformation” [Fuel 376 (2024) 132743] - Wenhu Yang; Yang Wu; Chengsong Huang; Yang Xu; Yaliu Zhang; Bingcheng Wu; Xingmei Wang; Lin Zhong; Jianli Wang; Yaoqiang Chen (Fuel, 2024)

Emission, distribution and formation characteristics of polybrominated dibenzo-p-dioxins and dibenzofurans during co-disposal of hexabromocyclododecane-containing waste in cement kiln - Jian Wang; Bingcheng Lin; Xiao Wang; Guorui Liu; Rong Jin; Jukun Xiong; Jianping Guo; Yinming Li; Minghui Zheng (Science of The Total Environment, 2024)

Emission characteristics and process distributions of multiple brominated persistent organic pollutants during co-disposal of hexabromocyclododecane-containing waste in a municipal solid waste incinerator - Wenhui Xie; Bingcheng Lin; Yaqi Peng; Bei Chen; Yuchun Wang; Yuxuan Ying; Shengyong Lu; Tong Chen (Journal of Environmental Management, 2024)

Magnesium-endowed exceptional hydrothermal stability of Pd/CeO2-ZrO2-Al2O3 catalyst for low-concentration methane combustion via two-step structure transformation - Wenhu Yang; Yang Wu; Chengsong Huang; Yang Xu; Yaliu Zhang; Bingcheng Wu; Xingmei Wang; Lin Zhong; Jianli Wang; Yaoqiang Chen (Fuel, 2024)

Insight into the inhibition mechanisms of Ca-, N-, S-containing compounds on persistent organic pollutant formation from the thermal reaction of anthracene on copper chloride - Xiao Wang; Bingcheng Lin; Jian Wang; Yunfeng Ma; Rong Jin; Guorui Liu; Minghui Zheng (Chemical Engineering Journal, 2024)

Characteristics and degradation mechanisms of polychlorinated naphthalenes in surface soil in Yangtze River Delta, China - Zherui Zhang; Guohua Zhu; Yahui Liu; Xin Zhou; Bingcheng Lin; Ziyuan Qi; Shanshan Zhang; Yueyao Yang; Xin Li; Rong Jin; Minghui Zheng (Chemosphere, 2024)

Model Evaluation of Indoor Exposure to Polychlorinated Dibenzo-p-Dioxins and Dibenzofurans and Polycyclic Aromatic Hydrocarbons from Household Fuel Combustion in Rural Areas of Tibetan Plateau - Rong Jin; Minghui Zheng; Lili Yang; Gerhard Lammel; Xin Zhou; Yuxiang Sun; Changzhi Chen; Bingcheng Lin; Guorui Liu (Exposure and Health, 2023)

Free radical mechanism of toxic organic compound formations from o-chlorophenol - Xiaoyun Liu; Guorui Liu; Shuting Liu; Linjun Qin; Bingcheng Lin; Mingxuan Wang; Lili Yang; Minghui Zheng (Journal of Hazardous Materials, 2023)

Concentrations, congener patterns, and correlations of unintentional persistent organic pollutants in cement kilns co-processing hazardous waste - Changzhi Chen; Haoyang Wang; Guorui Liu; Bingcheng Lin; Lili Yang; Rong Jin; Yuxiang Sun; Jianping Guo; Yinming Li; Nan Yang; Aihong Li; Changliang Li; et al. (Science of The Total Environment, 2023)

Machine learning-driven evaluation and optimisation of compression yielded FRP-reinforced concrete beam with T section - Bingcheng Guo; Xiaoshan Lin; Yufei Wu; Lihai Zhang (Engineering Structures, 2023)

Multi‐omic analyses of exogenous nutrient bag decomposition by the black morel Morchella importuna reveal sustained carbon acquisition and transferring - Hao Tan; Annegret Kohler; Renyun Miao; Tianhai Liu; Qiang Zhang; Bo Zhang; Lin Jiang; Yong Wang; Liyuan Xie; Jie Tang; Xiaolin Li; Lixu Liu; et al. (Environmental Microbiology, 2019)
Summary The black morel ( Morchella importuna Kuo, O'Donnell and Volk) was once an uncultivable wild mushroom, until the development of exogenous nutrient bag (ENB), making its agricultural production quite feasible and stable. To date, how the nutritional acquisition of the morel mycelium is fulfilled to trigger its fruiting remains unknown. To investigate the mechanisms involved in ENB decomposition, the genome of a cultivable morel strain ( M . importuna SCYDJ1‐A1) was sequenced and the genes coding for the decay apparatus were identified. Expression of the encoded carbohydrate‐active enzymes (CAZymes) was then analyzed by metatranscriptomics and metaproteomics in combination with biochemical assays. The results show that a diverse set of hydrolytic and redox CAZymes secreted by the morel mycelium is the main force driving the substrate decomposition. Plant polysaccharides such as starch and cellulose present in ENB substrate (wheat grains plus rice husks) were rapidly degraded, whereas triglycerides were accumulated initially and consumed later. ENB decomposition led to a rapid increase in the organic carbon content in the surface soil of the mushroom bed, which was thereafter consumed during morel fruiting. In contrast to the high carbon consumption, no significant acquisition of nitrogen was observed. Our findings contribute to an increasingly detailed portrait of molecular features triggering morel fruiting.